Identifikasi Peran Masyarakat Dalam Implementasi Kebijakan Pembangunan Hutan Kota Pekanbaru Provinsi riau - hutasoit, Anastasia; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The Pekanbaru city forest is one of the open green space alternatives in solvingenvironmental problems in urban areas, especially Pekanbaru. The existence of the forest city is stated in the Government Regulation No. 63 of 2002. The role of the civil society is needed in the policy implementation for the Pekanbaru city forest development. This research aimed to know the problems occurred through a society approach in the management of city forest and know the society role in the implementation of the policy of the Government Regulation No. 63 of 2002 of City Forest. This research was carried out in Jalan Thamrin the city forest of Pekanbaru Riau Province. The research used survey method with quantitative and qualitative analysis techniques. Quantitative analysis used the percentage formula for the assessment of the role of society against the tendency of the management of city forest. Qualitative analysis explained the implementation of the society role in the city forest management in the Government Regulation No. 63 of 2002 about city Forest. The research results indicated three problems in Pekanbaru city forest are the public ignorance about the Government Regulation No. 63 of Forest City policy, the lack of infrastructure support and the limited maintenance fund of the city forest. The problems hamper the implementation of the Government Regulation No. 63 of 2002 about city forest which indicated the absence of the role of society in the Pekanbaru city forest development . Keywords : city forest, policy, development, society role.